Impact of improved hermetic storage on food insecurity and poverty of smallholder cowpea farmers in northwestern Nigeria - Adomi, A.A.; Abdoulaye, Tahirou; Mohammed, A.B.; Abdu, Z.; Musa, S.A.; Baributsa, D. (Elsevier, 2023)
Postharvest loss of cowpea grains due to insect pests like cowpea bruchids is a common problem in Nigeria and has often exacerbated the food insecurity and poverty of households. In a bid to protect their cowpea grains, farmers’ indiscriminate use of insecticides (often misused and overused) has had a negative impact on human health and the environment. Efforts to promote the use of non-chemical hermetic storage have sought to address the issue. This study, therefore, examined the impact of a chemical-free, hermetic storage method, the Purdue Improved Crop Storage (PICS) bags, on food insecurity and poverty of smallholder cowpea farmers in Northwestern Nigeria. Household food expenditure analysis revealed that PICS adopters had higher food security than non-adopters. Similarly, poverty analysis showed that PICS adopters had a lower poverty incidence than non-adopters. Government and development agencies should, therefore, promote the use of PICS to improve food security and reduce poverty among cowpea farmers in Nigeria.